2001
DOI: 10.1080/02844310151032691
|View full text |Cite
|
Sign up to set email alerts
|

Acute Postoperative Swelling After Hand Surgery: An Exploratory, Double-Blind, Randomised Study With Paracetamol, Naproxen, and Placebo

Abstract: A model using volumetry to evaluate the effect of drugs on acute postoperative swelling after operations for primary Dupuytren's contracture (DC) and carpal tunnel syndrome (CTS) was established and validated. The temperature of the saline and time of measurement during the day influenced the volumetric readings. The error of measurement after volumetry of unoperated and operated hands after operations for DC was 0.7% and 0.6%, respectively. Naproxen (500 mg twice a day), paracetamol (1000 mg four times a day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In another study of the same authors, 1000 mg acetaminophen was demonstrated to have preferable anti-inflammatory effects in comparison to 600 mg ibuprofen ( 11 ). Nonetheless, there are studies reporting that acetaminophen used at high doses had no preventable effect on swelling ( 27 ). According to the results of our study, 300 mg acetaminophen exhibited approximate clinical results with 12.5 mg DT, a NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of the same authors, 1000 mg acetaminophen was demonstrated to have preferable anti-inflammatory effects in comparison to 600 mg ibuprofen ( 11 ). Nonetheless, there are studies reporting that acetaminophen used at high doses had no preventable effect on swelling ( 27 ). According to the results of our study, 300 mg acetaminophen exhibited approximate clinical results with 12.5 mg DT, a NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding multimodal pain management strategies would prove helpful to hand surgeons as well. [63][64][65][66] Lastly, protocols for dressing following carpal tunnel surgery should be better studied. Removal of the bulky dressing before 72 hours has not been shown to cause wound complications.…”
Section: Future Research Directionsmentioning
confidence: 99%